Lodgepole pine regeneration after mountain pine beetle and wildfire: a case study in the High Park Fire, CO - Wright, Micah, author; Rocca, Monique, advisor; Rhoades, Charles, committee member; Hoffman, Chad, committee member (Colorado State University. Libraries, 2016)
The 2012 High Park Fire burned over 35,000 hectares, including 5,000 hectares of lodgepole pine (Pinus contorta) forest that had recently been attacked by mountain pine beetle (MPB, Dendroctonus ponderosae). This sequence of events provided an excellent opportunity to investigate the effects of combined disturbance on lodgepole pine regeneration trajectories. I examined the influence of MPB mortality, high canopy fire severity, site characteristics, and post fire mulching treatments on lodgepole pine recovery at both landscape (∼hectare) and fine (∼cm) spatial scales. At the landscape scale, lodgepole pine seedling densities varied from 240 to 470,000 stems/ha. Seedling densities decreased as MPB mortality and high canopy fire severity increased. At the fine scale, lodgepole pine seedling establishment was positively related to local cone abundance and negatively related to high canopy fire severity. Topographic variables such as aspect and elevation did not have a strong influence on seedling density or establishment at either scale, nor did competition from recovering vegetation have an influence at the fine scale where it was considered. In areas with high canopy fire severity, post-fire straw mulching treatments were positively related to seedling establishment, indicating that mulching treatments may have additional benefits beyond erosion control. My research demonstrates that combinations of pre-fire mountain pine beetle mortality and high canopy fire severity can affect lodgepole pine regeneration, and may drive heterogeneity in the post-fire landscape.